Excel Solver Aided Biogas Kinetics Computation for Varied Ratio Co-digestion of Cassava Peels with Chicken Manure - Luka, Yusufu; Saddiq, Hassan Ahmed; Abubakar, Abdulhalim Musa; Naandeti, Nathan Akucha (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
Existing biogas kinetic models require computational expertise. This study presents an Excel Solver-based approach to improve accessibility and accuracy. The co-digestion of cassava peels (CP) and chicken manure (CM) represents a sustainable approach to biogas production; however, optimizing process conditions and kinetic modeling remain crucial for efficiency. The study employed Excel Solver to estimate kinetic parameters in the modified Gompertz and Cone models for three different CP:CM ratios (1:1, 1:3, and 3:1) under mesophilic conditions (ambient temperature) and a retention time of 40 days. Anaerobic digestion (AD) was conducted in 4-L batch digesters with a working volume of 2 L. Results showed that the 1:3 CP:CM ratio produced the highest cumulative biogas yield (0.25 m³) from the experiment, outperforming the other ratios (1:1 = 0.2384 m³ & 3:1 = 0.1576 m³). At the optimal ratio, the modified-Gompertz model exhibited a superior fit (R² = 0.9684) compared to the Cone model (R² = 0.7586), with lower SSE values (2.157 vs. 16.503, respectively), confirming its reliability in capturing microbial adaptation and substrate degradation dynamics. The estimated parameters—biogas production potential (BP = 0.2076 m³), maximum production rate (k = 0.0226 m³/day), and lag phase (λ = 3.4 days)—highlighted the significance of nitrogen balance in optimizing biogas yield. The kinetic study is essential for predicting biogas production trends, optimizing digester performance, and designing efficient biogas systems. The Excel Solver, provided, is a user-friendly tool for nonlinear regression, eliminating the need for specialized statistical software.